Pendampingan Guru dalam Peningkatan Pengetahuan tentang Penilaian Status Gizi - Firnaliza Rizona; Yeni Anna Appulembang; Fuji Rahmawati; Sigit Purwanto; Khoirul Latifin (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
Obesity prevalence on school age children was increasing especially in pandemic covid 19 because of online lesson which make the physical activity become subtract. Early preventing should be conduct to decrease obesity till adult age and other health effect which is could disturb children healthy. Early detection obesity by the school can be done through nutritional status data collection of students. But a lot of schools did not know how to determine children nutritional status. Subject of this community dedication was the teacher in elementary school to increase the knowledge on measure the student’s nutritional status. This training was completed with media such us guideline book for determining nutritional status. Teacher conducted the small group discussion divided to five personal in four group. The result of this activity was increasing knowledge of teacher in determining the student’s nutritional status. Based on this activity The objective of this public service is elementary school teacher to increase knowledge in measuring the status of child nutrition. Based on these activities are on the schools regularly can do early detection at the nutritional status students to children with the risk of obesity and that has been obese can get immediate intervention and the school can collaborate with health services to tackle obesity on a student.